Migration and morphometrics of the Red-breasted Merganser Mergus serrator in northern Eurasia and the implications for conservation of this species in Britain and Ireland - Robinson, J A (Wildfowl, 1999)
Criterion 3c of the Ramsar Convention on wetlands of international importance suggests that a wetland should be considered internationally important if it regularly supports 1% of the individuals in a population of a species or subspecies of waterfowl. A review of the status of Red- breasted Merganser Mergus serrator populations in Europe was conducted to investigate how the 1% threshold for this species should be determined for the UK. Four discrete breeding populations of the nominate race of the Red-breasted Merganser have been identified in northern Eurasia. Ringing recoveries indicate that some birds from the Iceland, east Greenland, Britain and Ireland group are dispersive within their own countries in the non-breeding season whereas others move to coastal waters around Iceland, Britain and Ireland. There is a small amount of evidence, from ringing recoveries and systematic counts, of interchange between birds from this group and those from the rest of north-west Europe. For the designation/identification of 1% thresholds in the UK, the evidence available at present suggests that the north-west and central European population should not be considered separate from those birds which breed in Iceland, east Greenland, Britain and Ireland. However, caution should be taken when interpreting these data and further studies are urgently required to clarify this matter.